Development Strategies of a National Company in Transnational Oligopolistic Market: The Case of Cooperative Pascual - G., José; Vargas-Hernández (International Journal For Research In Business, Management And Accounting, 2015)
The objective of this paper is to analyze the success reached due to the implementation of thestrategies used by Cooperativa Pascual. An analytic approach is used to understand it’s mostimportant problematic. After the labor shortcut in 1982 and posterior worker´s strike that lastedmore than 3 years that lead to the delivery of the company assets to the workers, the firm changedits name from “Pascual S.A.” to “Cooperativa Pascual”. Despite all this struggles, the companycould perform as one of the best firms at national level in the beverage industry. CooperativaPascual is an example of strategy application in companies, because it competes with some of thebiggest transnational like Coca-Cola, Pepsi, and others.